Rosai-Dorfman disease presenting as mediastinal lymphadenopathy: case report and review of the literature. (1st May 2013) - Cobanoglu, Nazan; Galip, Nilufer; Dalkan, Ceyhun; Comunoglu, Cem; Bahceciler, Nerin
<x xml:space="preserve">Abstract</x> A 6-year-old boy presented with recurrent pneumonia and diarrhoea for 3 years. He had extensive mediastinal lymphadenopathy and atelectasis with low serum levels of IgA, IgG and IgG3. An inguinal lymph node biopsy demonstrated histological and histochemical features of Rosai-Dorfman disease. There was emperipolesis and histiocytes were immune-positive for S100 proteins. He responded to corticosteroids and regular infusions of immunoglobulins.